2016
DOI: 10.1016/j.injury.2016.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Total hip replacement for neck of femur fracture: Comparing outcomes with matched elective cohort

Abstract: Introduction: Current literature suggests that total hip replacement (THR) is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 35 publications
2
8
1
Order By: Relevance
“…In the RCT by the HEALTH investigators, the incidence of periprosthetic fracture within two years of hip fracture surgery was 5.3% for THA and 4.8% for hemiarthroplasty [ 8 ]. The rate of periprosthetic fracture reported in the present study is comparable to that reported for elective primary THA [ 18 , 25 ]. Meek et al reported a periprosthetic fracture incidence of 0.9% five years post-primary elective THA in a registry study of over 50,000 THAs [ 26 ].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In the RCT by the HEALTH investigators, the incidence of periprosthetic fracture within two years of hip fracture surgery was 5.3% for THA and 4.8% for hemiarthroplasty [ 8 ]. The rate of periprosthetic fracture reported in the present study is comparable to that reported for elective primary THA [ 18 , 25 ]. Meek et al reported a periprosthetic fracture incidence of 0.9% five years post-primary elective THA in a registry study of over 50,000 THAs [ 26 ].…”
Section: Discussionsupporting
confidence: 85%
“…The rate of dislocation in this study is similar or less than published rates of dislocation for conventional THA for hip fracture [ 9 , 12 , 18 ]. In a meta-analysis comparing THA to hemiarthroplasty for hip fracture, Lewis et al reported a dislocation rate of 8.1% in 591 THA compared to 2.7% in 630 hemiarthroplasties with varying durations of follow-up [ 4 ].…”
Section: Discussionsupporting
confidence: 77%
“…In literature, good results with DMC implants were reported in either FNF [ 20 , 21 , 22 ] or other conditions at increased risk for dislocation [ 10 ]. However, there are few retrospective and some register studies comparing DMC THA and standard THA in FNF [ 17 , 23 , 24 , 25 ], despite it being known that THA for fractures has a higher risk of dislocation than THA for osteoarthritis [ 26 , 27 , 28 ]. This risk could be related to different predisposing conditions observed in FNF patients, such as a good preoperative hip ROM, the prevalence of recurrent falls in older patients or the frequent postoperative delirium that compromises adherence to rehabilitation programs [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The comparison of hospital results based on Ŝ i (t) presented in the previous section does not account for systematic differences between groups of patients across hospitals, which may be necessary for some of the considered types of implantations. For hip replacements, for instance, readmission rates are known to be lower for elective operations compared to implantations for the treatment of femoral fractures (Lim et al 2016). Thus, hospital results should be compared under consideration of their respective patient population (Iezzoni 2013).…”
Section: Estimating Hospital-specific Effects On the Hazard Functionmentioning
confidence: 99%